2019
DOI: 10.1016/j.jdent.2019.103198
|View full text |Cite
|
Sign up to set email alerts
|

Childhood negative dental experiences and tooth loss in later life: A 25-year longitudinal study in Sweden

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
(36 reference statements)
1
4
0
4
Order By: Relevance
“…Frequency of dental visits within the past year did not play a role in the association between early negative dental care experience and tooth loss in that study. 27 In accordance with the study of Bernabe et al, 27 studies reported by Vettore et al 9 and Vendrame et al 28 could not verify assumptions of indirect effects through behaviours in the association between childhood socio-economic position and adult oral health. By contrast, Celeste et al, 29 revealed that a minor amount of 1.4% of ethnic disparity in tooth loss was explained by the combination of dental visits, marital status and alcohol consumption.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Frequency of dental visits within the past year did not play a role in the association between early negative dental care experience and tooth loss in that study. 27 In accordance with the study of Bernabe et al, 27 studies reported by Vettore et al 9 and Vendrame et al 28 could not verify assumptions of indirect effects through behaviours in the association between childhood socio-economic position and adult oral health. By contrast, Celeste et al, 29 revealed that a minor amount of 1.4% of ethnic disparity in tooth loss was explained by the combination of dental visits, marital status and alcohol consumption.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies, using various approaches to mediation analysis, have documented on the direct and indirect associations between childhood experiences and oral health. 18,26,27 In a prospective study of Swedish adults, Bernabe et al 27 observed a long-lasting, damaging effect of negative dental experiences in childhood on tooth loss at older ages. Frequency of dental visits within the past year did not play a role in the association between early negative dental care experience and tooth loss in that study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Önnur saensk rannsókn leiddi í ljós að 11% karla og 15% kvenna á aldrinum 25-35 ára forðuðust að leita til tannlaeknis vegna ótta í kjölfar óþaegilegrar reynslu af tannlaeknaþjónustu í aesku (Åstrøm, Sulo, Smith, 2019, ekki enn birt). Í hópi eldra fólks í Svíþjóð mátti einnig sjá tilhneigingu til að forðast að leita tannlaeknis vegna ótta þegar um var að raeða slaema upplifun af tannlaeknaþjónustu í barnaesku (39). Í Svíþjóð (9), á Íslandi, í Finnlandi ( 14) og Danmörku (30,40) hefur komið í ljós að konur leita oftar tannlaeknis en karlar.…”
Section: þAettir Sem Tengjast Nýtingu Tannlaeknaþjónustuunclassified
“…Í löndum þar sem tekjur eru háar eru fyrirbyggjandi heimsóknir algengari, og tengsl eru milli tíðrar aðsóknar annars vegar og faerri sjúkdóma í munni og betri munn-og tannheilsu hins vegar. Nokkrar nýlegar hóprannsóknir með þversniði hjá fullorðnum í Noregi hafa sýnt fram á að neikvaeð upplifun af tannlaeknaþjónustu í barnaesku eykur líkur á að forðast sé að leita til tannlaeknis, sem aftur eykur tíðni tanntaps (39).…”
Section: Heimildirunclassified